Community University Research Agreement - Priscilla Settee; Shelley Thomas-Prokop (The Australian Journal of Indigenous Education, 2007)
Abstract This paper describes the process of engaging the extended Indigenous community within Saskatoon and the surrounding First Nations communities in what would be a first major research project between Indigenous communities and the University of Saskatchewan. A management committee was established comprised of all the major Saskatoon/Saskatchewan Indigenous organisations, such as the Federation of Saskatchewan Indians, Saskatoon Tribal Council, First Nations University of Canada and other community-based groups to ensure that research reflected First Nations and Metis needs. The project called “Bridges and Foundations” awarded some 35 projects close to two million dollars in research funds. The money was awarded through graduate student research bursaries, and community-based projects which highlighted the needs of Indigenous women, youth, students, elders and urban populations. The three research themes included respectful protocol, knowledge creation, and policy development. The research projects, which were largely Indigenous designed and driven, created one of the most extensive research collections over a period of four years and included major data collection on community-based research, Indigenous peoples and Indigenous knowledge systems and protocols. The paper relates the development of the project and speaks about the need for Indigenous peoples to lead their own research as well as the benefits of collaboration. It also highlights several of the research projects including a conference on Indigenous knowledge (2004), a video project describing the community mobilisation process behind Quint Urban Housing Co-operatives